(3GdeONd Gdi GdbGfhf (B:s (3GdbGYOI GdbGfhfjI(B- (3fXQjI GdMb (B/s - (3efUhQ, eMeO MSjfs; (3bGSe, eMeO MSjf s ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3eGgjI GdMb, hLhO GdMb, ecGfI GdMb aj GdfXGe GdbGfhfj GdeYGUQ(B- (3WHGFY GdMbhb hJbSjeGJgG, CfhGY GdMbhb(B- (3GdGTjGA eMd GdMb(B- (3ejdGO GdMb hMeGjJg, GdTNUjI GdbGfhfjI, GdTNU GdeYfhj Ch GdEYJHGQjs
Keywords: (3GdbGYOI GdbGfhfjIs; (3GdbGfhfs